Improving the quality of the rhythmic female gymnasts feet performance by the means of traditional choreography - Rumba, O. (Science of Gymnastics Journal, 2013)
In the article we prove empirically that the feet performance quality is the significant constituent part of the sport skills in gymnastics and among the other components it has influence on gymnasts` success in competitions. Through the survey of the gymnastics specialists we determine the key-points of the female gymnasts` feet performance quality. According to the received data they are the height of rising to half toe position; the capacity to perform for a long time on one foot and maintain its turnout and the height of half toe position; the capacity to balance for a long time in high turnout half toe position; the degree of toe pointing; feet turnout. We explain the chosen check tests that let estimate the performance degree of all the indexes of the female gymnasts` feet performance quality. With determining the most effective exercises of traditional choreography we develop the methods of improving the female gymnasts` feet performance quality. The effectiveness of the developed methods is examined through the educational experiment.